Spatiotemporal Control of Morphogen Delivery to Pattern Stem Cell Differentiation in Three‐Dimensional Hydrogels. (5th September 2019) - O'Grady, Brian J.; Balikov, Daniel A.; Lippmann, Ethan S.; Bellan, Leon M.
Abstract: Morphogens are biological molecules that alter cellular identity and behavior across both space and time. During embryonic development, morphogen spatial localization can be confined to small volumes in a single tissue or permeate throughout an entire organism, and the temporal effects of morphogens can range from fractions of a second to several days. In most cases, morphogens are presented as a gradient to adjacent cells within tissues to pattern cell fate. As such, to appropriately model development and build representative multicellular architectures in vitro, it is vital to recapitulate these gradients during stem cell differentiation. However, the ability to control morphogen presentation within in vitro systems remains challenging. Here, we describe an innovative platform using channels patterned within thick, three‐dimensional hydrogels that deliver multiple morphogens to embedded cells, thereby demonstrating exquisite control over both spatial and temporal variations in morphogen presentation. This generalizable approach should have broad utility for researchers interested in patterning in vitro tissue structures. © 2019 by John Wiley & Sons, Inc.